The Relationship Between Caffeine Intake And Gastritis Symptoms Among Final-Year University Students - Maria Della Imersi Naben; Firman Firdauz Saputra; Pesona Dessritina (Journal of Food, Nutrition, and Health Advances, 2026)
Gastritis is a condition characterised by inflammation of the gastric mucosa (stomach lining), marked by nausea, vomiting, weakness, and abdominal discomfort. The incidence of gastritis in Indonesia is relatively high, with a prevalence of 274,396 cases amongst a population of 238,452,952. This study aims to analyse the relationship between caffeine consumption and gastritis symptoms among university students. This is a quantitative study with a cross-sectional design. The population comprised all students at Teuku Umar University, and the sample was selected using time-based accidental sampling. Specifically, between March and April 2026, 308 respondents who met the inclusion criteria were recruited during the data collection period. Data were collected using a questionnaire covering respondent characteristics, caffeine consumption, and gastritis symptoms. Data analysis was conducted using univariate analysis to describe each variable and bivariate analysis with the chi-square test to assess relationships between variables. The results showed a significant association between caffeine consumption and gastritis symptoms (p-value = 0.008). This study concludes that there is a significant association between caffeine consumption and gastritis symptoms. Therefore, students are advised to limit the amount and frequency of their caffeine consumption as a preventive measure against gastritis.